2018
DOI: 10.1016/j.jcrs.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical versus transepithelial phototherapeutic keratectomy epithelial removal followed by accelerated corneal crosslinking for pediatric keratoconus: Long-term results

Abstract: The initial visual and topographic outcomes of transepithelial PTK ablation were better than those of mechanical epithelium removal before accelerated CXL in pediatric patients with keratoconus. Over the long-term, the results were similar between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Excimer laser ablation combined with CXL treatment has been proposed as an ideal technique due to its optimal refractive outcome that can provide both stability and functional vision, by both stabilizing and reshaping the cornea [ 25 ]. Previous studies also suggested that the CXL-plus-PTK procedure is more effective than the S-CXL procedure [ 26 , 27 ]. Further, the improved efficacy could last up to 2 years after surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excimer laser ablation combined with CXL treatment has been proposed as an ideal technique due to its optimal refractive outcome that can provide both stability and functional vision, by both stabilizing and reshaping the cornea [ 25 ]. Previous studies also suggested that the CXL-plus-PTK procedure is more effective than the S-CXL procedure [ 26 , 27 ]. Further, the improved efficacy could last up to 2 years after surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While excimer lasers have been used to perform full epithelial debridement, to our knowledge, this is the first study to apply an excimer laser in order to create small epithelium penetrating channels (Kanellopoulos & Asimellis 2014 ; Sarac et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They show stromal RF concentrations of approximately 50% the concentration after regular epi-off protocols, but biomechanical effects are not reported on. While excimer lasers have been used to perform full epithelial debridement, to our knowledge, this is the first study to apply an excimer laser in order to create small epithelium penetrating channels (Kanellopoulos & Asimellis 2014;Sarac et al 2018).…”
Section: Strip Extensiometrymentioning
confidence: 99%
“…TCT only returned to preoperative values after 5 years. Sarac et al 31 performed CCL using mechanic or phototherapeutic keratectomy and observed significant decreases in TCT at postoperative 3 years in both groups. Wittig-Silva et al 32 performed CCL using a modified Dresden Protocol and reported that at 3-year follow-up, TCT measured by ultrasonic pachymetry was significant reduced in the control group and unchanged in the CCL group, whereas TCT measured using Orbscan computerized videokeratography showed significant decreases, consistent with our study.…”
Section: Discussionmentioning
confidence: 99%